Faktor yang Mempengaruhi Kinerja Guru di SMA Intensif Taruna Pembangunan Surabaya: Faktor yang Mempengaruhi Kinerja Guru di SMA Intensif Taruna Pembangunan Surabaya - Bisma Arianto; Siti Samsiyah (.Universitas PGRI Adi Buana, 2023)
This study aims to analyse the effect of motivation, work discipline and work environment on teacher performance at Intensif Taruna Pembangunan High School Surabaya. This research includes population research which is used as a research sample on 60 respondents with random sampling technique. For the method used in this study is the classical assumption test which is strengthened by normality test, heteroscedastity test, multicolinerity test. The results of these findings indicate that work motivation, work discipline and work environment have a positive and significant direct influence on teacher performance. The results of this study recommend that schools provide opportunities and motivate teacher to improve work results in supporting school goals.